2020
DOI: 10.1039/d0ta08006c
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Cu2S@NiCo-LDH double-shelled nanotube arrays with enhanced electrochemical performance for hybrid supercapacitors

Abstract: Hierarchical nanotube arrays with complex shell structures are attractive for applications in electrode materials for effectively boosted electrochemical performance, but the construction of such delicate architectures with excellent electrochemical performance...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(88 citation statements)
references
References 63 publications
0
88
0
Order By: Relevance
“…The fitted data demonstrated Warburg resistance of the NSC and NCuSC electrodes were almost same and decreased in the NCoSC electrode. The lower W o value of the NCoSC electrode signified facile and shorter ion diffusion path to the active electrode material with more ideal capacitive behavior compared to the other two electrodes [2][3][4][5][6]31,38]. Electrochemical measurement suggested that the NCoSC material showed superior performance as compared to the NSC and NCuSC electrodes.…”
Section: Electrochemical Characterization Of Electrodesmentioning
confidence: 98%
See 4 more Smart Citations
“…The fitted data demonstrated Warburg resistance of the NSC and NCuSC electrodes were almost same and decreased in the NCoSC electrode. The lower W o value of the NCoSC electrode signified facile and shorter ion diffusion path to the active electrode material with more ideal capacitive behavior compared to the other two electrodes [2][3][4][5][6]31,38]. Electrochemical measurement suggested that the NCoSC material showed superior performance as compared to the NSC and NCuSC electrodes.…”
Section: Electrochemical Characterization Of Electrodesmentioning
confidence: 98%
“…Higher retention of capacitance of NCoSC is attributed to the synergistic effect between the transition metals carbon coating. Improvement in electrical conductivity is attributed to the interconnected network structure of NCoSC electrode, contributing to achieving higher electrochemical properties [4][5][6]12,32,38]. EIS is a principal method to measure the internal resistance and ion diffusion properties of the materials.…”
Section: Electrochemical Characterization Of Electrodesmentioning
confidence: 99%
See 3 more Smart Citations